Students' conceptual understanding in chemistry learning using PhET interactive simulations - Yuli Rahmawati; Zulhipri Zulhipri; Octaviano Hartanto; Ilham Falani; Deni Iriyadi (OmniaScience, 2022)
This study aims to analyse students' conceptual understanding of chemical equilibrium matter using Physics Education Technology (PhET) Interactive Simulations. Students' misconceptions can be caused by the difficulty in connecting the sub-microscopic, macroscopic, and symbolic levels of understanding in chemistry. The study was conducted at a secondary school with a total sample of 108 students using a quantitative research method. The results showed that multiple-choice questions of the two-tier Chemical Equilibrium Diagnostic Instrument (CEDI) used in this study meet with the Rasch measurement model. The students who answered correctly on content knowledge ranged from 11.1-90.7%. However, the percentage decreased to 11.1-84.3% once the content knowledge and reasons were combined. The option probability curve responses identified the students' misconceptions that were further investigated by interviews. PhET Interactive Simulations require improvements or additional features to help students better understand conceptual understanding through analogies of product and reactant molecules' movement in the equilibrium system.